1992
DOI: 10.1111/j.1432-1033.1992.tb17252.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic properties are shifted back to agonistic properties by further N‐terminal shortening of pituitary adenylate‐cyclase‐activating peptides in human neuroblastoma NB‐OK‐1 cell membranes

Abstract: ) -EJB 92 0760 N-terminally shortened analogs of the 27-amino-acid and 38-amino-acid forms of the pituitaryadenylate-cyclase-activating neuropeptide, PACAP( 1 -27) and PACAP( 1 -38), were synthesized by a solid-phase method. Systematic deletion of the first 13 amino acids of both PACAP was tested by evaluating their ability to occupy the specific and selective PACAP receptor of human neuroblastoma NB-OK-1 cell membranes and to stimulate adenylate cyclase or, when inactive per se, to inhibit PACAP-stimulated ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…To identify which part of the PACAP molecule is responsible for the recognition of PACAP type 1-binding sites, PACAP and VIP sequences have been compared. It has been reported that replacement of Asp 9 and Leu 13 in VIP by serine and tyrosine, respectively, increased, by two to five times, the affinity of VIP for I-PACAP-binding sites (13,15). Maxadilan does not possess histidine in the corresponding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify which part of the PACAP molecule is responsible for the recognition of PACAP type 1-binding sites, PACAP and VIP sequences have been compared. It has been reported that replacement of Asp 9 and Leu 13 in VIP by serine and tyrosine, respectively, increased, by two to five times, the affinity of VIP for I-PACAP-binding sites (13,15). Maxadilan does not possess histidine in the corresponding site.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, as well as those of others, reveal that receptor binding affinity was higher with PACAP-38 than with PACAP-27. It has also been reported that the helix-breaking Gly 20 -Gly 21 substitution in PACAP-27 reduced the affinity of the resulting peptide 500-fold, indicating that the two highly hydrophilic residues (Lys 20 and Lys 21 ), located in the central portion of a hydrophobic domain in PACAP-27, were important for PACAP receptor recognition (13,15).…”
mentioning
confidence: 99%
“…Accordingly, PACAP-(1 -27)-peptide has a disordered N-terminal domain consisting of eight amino acids, followed by an a-helical structure stretching from Ser9 to Va126, which contains a discontinuity between Lys20 and Lys21. Previous data concerning the structural requirements of PACAP to recognize its receptor are primarily based on modifications of PACAP at its N-terminal part Vandermeers et al, 1992;Bitar et al, 1994). In the PACAP derivatives that we synthesized in this study, the amino acids Phe6 and Tyr22 were displaced by the photoreactive BzPhe thus leading to benzophenone-containing PACAP analogues with modifications in both domains of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of these receptors is a relatively large N-terminal extracellular region consisting of about 1.50 amino acids with several highly conserved cysteine residues. Some structural requirements for the occupancy of the PACAP type I receptors have been reported and led to the development of receptor antagonists Vandermeers et al, 1992;Bitar et al, 1994). By using chemical modification and deletion mutagenesis, we have previously demonstrated that the N-terminal fragment of the PACAP type I receptor contains a major binding site for its ligand (Cao et al, 1994(Cao et al, , 1995.…”
mentioning
confidence: 99%
“…PACAP38 and PACAP6-38 (Peptide Institute Inc., Osaka, Japan), a specific and selective receptor antagonist [13,17] were dissolved (0.25, 1, or 4 nmol/10 µl) in artificial cerebral spinal fluid [15,16]. Control animals received the same volume (10 µl) of vehicle.…”
Section: Methodsmentioning
confidence: 99%